Factors Affecting the Interpretation of Online Phycocyanin Fluorescence to Manage Cyanobacteria in Drinking Water Sources - Ma, Liya; Moradinejad, Saber; Guerra Maldonado, Juan Francisco; Zamyadi, Arash; Dorner, Sarah; Prévost, Michèle (Water, 2022)
Recently, in situ YSI EXO2 phycocyanin fluorescence probes have been widely deployed as a means to determine cyanobacterial abundance in drinking water sources, yet few studies have evaluated the effects of natural organic matter (NOM) and the ambient water temperature on the probe readings. In this study, Suwannee River NOM was added to laboratory cultivated cyanobacterial species to test the performance of the phycocyanin probe. The impact of temperature on phycocyanin fluorescence was evaluated by monitoring the laboratory cultivated cyanobacterial species and extracted phycocyanin pigment. Additionally, in situ phycocyanin fluorescence of the field samples from the water intake of a drinking water treatment plant (DWTP) in 2018 were compared with grab sample laboratory taxonomic analyses. We found: (1) the presence of Suwannee River NOM leads to the decrease in cell-bound cyanobacterial phycocyanin readings; (2) increasing ambient water temperature reduces dissolved and cell-bound cyanobacterial phycocyanin readings; (3) field study phycocyanin probe readings significantly correlated with the total cyanobacterial biovolume (R = 0.73, p < 0.1), and the relationship depends on the biovolume of dominant cyanobacterial species; (4) phycocyanin probe readings have a strong positive correlation with the natural light intensities; and (5) probe users should be fully aware of the sources of interferences when interpreting the results and apply the other physical-chemical parameters data simultaneously generated by the fluorometry to improve the probe’s measurements.
Keywords: Dorner_Sarah